Workshop Pengelolaan Kelas Berdiferensiasi dan Multikultural bagi Guru Sekolah Dasar di Kota Blitar - Barus, Yohannes Kurniawan; Mudiono, Alif; Ahdhianto, Erif; Khoiriya, Rika Mellyaning; Cahyani, Indah Galis; Ro'atin, Aniva Fitri Lite (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The diversity of student characteristics requires teachers to be able to manage the class well so that all students do not feel neglected and feel valued for their uniqueness. This activity aims to provide an understanding of elementary school teachers in Blitar City in managing differentiated and multicultural classes, to accommodate student diversity. The method used is a workshop that includes presentation activities and case study analysis attended by 28 elementary school teachers in Blitar City. The evaluations carried out include: reactions, knowledge, impacts, and final results using a Likert scale. The results show that teachers have understood the concept of differentiated learning and multicultural education and showed a high level of satisfaction, although further efforts are needed to deepen the application of strategies in the classroom.